Membrane Electrode Assembly for Electrocatalytic CO2 Reduction Principle and Application - Zhang Zheng; Huang Xin; Chen Zhou; Zhu Junjiang; Endrődi Balázs; Janáky Csaba; Deng Dehui (2023)
Electrocatalytic CO2 reduction reaction (CO2RR) in membrane electrode assembly (MEA) systems is a promising technology. Gaseous CO2 can be directly transported to the cathode catalyst layer, leading to enhanced reaction rate. Meanwhile, there is no liquid electrolyte between the cathode and the anode, which can help to improve the energy efficiency of the whole system. The remarkable progress achieved recently points out the way to realize industrially relevant performance. In this review, we focus on the principles in MEA for CO2RR, focusing on gas diffusion electrodes and ion exchange membranes. Furthermore, anode processes beyond the oxidation of water are considered. Besides, the voltage distribution is scrutinized to identify the specific losses related to the individual components. We also summarize the progress on the generation of different reduced products together with the corresponding catalysts. Finally, the challenges and opportunities are highlighted for future research.
Keywords: Kémiai tudományok